Kosmologi Penciptaan Laki-Laki dan Perempuan dalam Tafsir Maqāṣidī: Respon terhadap Kesetaraan Gender - Mursalim; Nurul Hasanah (STAI DDI Makassar, 2023)
Gender equality is a concept advocated by feminists, aiming to achieve equal rights and opportunities for women, who have historically faced discrimination from men due to patriarchal cultural norms. This research utilizes a qualitative-descriptive method, seeking to explain the phenomenon of gender equality from the perspective of Islamic cosmological science and employing the method of tafsir maqasidi. The findings of this research indicate that in cosmology, both men and women are interconnected with the cosmic universe. The creation of the universe represents the manifestation of Allah SWT's names